(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article "Augmented Reality Translation: How Technology is Changing the Way We Look at Language Barriers" explores the role of augmented reality (AR) in the field of translation. It discusses the benefits, such as immersive experiences, real-time capability and multimodality, as well as the challenges, including speech recognition accuracy and cultural nuance adaptation. The article also presents the future prospects for AR in translation, including improved mobile applications, educational opportunities, and medical applications. Finally, it concludes that translation AR is not just a tool, but a new way of seeing and interacting with the world that can greatly enrich our intercultural communication and make it more accessible to all.